Effect of electroacupuncture versus sham electroacupuncture on postoperative ileus after laparoscopic surgery for left-sided colorectal cancer: study protocol for a multicentre, randomised, sham-controlled trial - Wei Dai; Fang Liu; Fan-rong Liang; Jie Lin; Chen Yang; Jiao Yang; Lin Han; Yan Zhou; Yang-yang Wang; Mingming Zhang; Xu Guixing; Shu-Hao Li; et al. (BMJ Open, 2024)
Introduction Postoperative ileus (POI) is an inevitable complication after abdominal surgery, often hindering recovery and prolonging hospital stay. Despite the increasing use of electroacupuncture (EA) as an alternative treatment for gastrointestinal dysfunction, its effectiveness for POI is still controversial. This study aims to verify the efficacy and safety of EA in alleviating POI.Methods and design The study is a multicentre, randomised, sham-controlled trial. A total of 174 patients undergoing laparoscopic surgery for left‐sided colorectal cancer will be randomly assigned to an EA group and a sham acupuncture group at a ratio of 1:1. Treatment for both groups will commence on the first day after the operation and continue once a day for four consecutive days. The primary outcome is time to first defecation. Secondary outcomes include time to first flatus, time to first tolerance to liquid and semiliquid diet, Functional Assessment of Cancer Therapy-Colorectal (FACT-C, V.4.0), postoperative nausea and vomiting, postoperative pain and abdominal distension, the Gastrointestinal Quality of Life Index, Self-Rating Depression Scale, Self-Rating Anxiety Scale, Gastrointestinal Symptom Rating Scale, length of the postoperative hospital stay, time to first postoperative ambulation, evaluation of the expected value of acupuncture, and satisfaction evaluation.Ethics and dissemination The results will be disseminated through peer-reviewed publications. This study protocol (V.2.0, 1 October 2023) involves human participants and has been approved by the Ethics Committee of Sichuan Cancer Hospital (number KY-2023-041-01), Meishan Hospital of Traditional Chinese Medicine (number 2024LC001) and The Seventh People’s Hospital of Chengdu (number KY2024-001-01). Each individual who agrees to participate in the research will provide written informed consent after the objectives and procedures of this study are explained to them.Trial registration number ChiCTR2400079645. Registered on 8 January 2024.